2022
DOI: 10.1177/08862605211055155
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Forced Sexual Experiences Among High School Students From 2001 to 2019

Abstract: Public awareness of sexual assault and initiatives aimed at preventing sexual assault continue to increase over the years. However, whether rates of sexual assault have diminished because of such cultural shifts remains unclear. The purpose of this study was to assess if rates of sexual assault (i.e., forced sex) have changed over the past 18 years for adolescent girls and boys as well as potential differences across racial/ethnic identities. Using nationally representative data from the Youth Risk Behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Our findings also carry important clinical implications, including the application of this knowledge to the development of risk-reduction programs for college women. Although the need for risk-reduction programs (e.g., those aimed at improving risk perception) would be eliminated if perpetrators ceased to engage in sexually aggressive behaviors (Orchowski & Gidycz, 2018), it is important to note that perpetrator interventions have been largely unsuccessful in producing long-term reductions in rates of violence (Orchowski & Berkowitz, 2022), resulting in stable rates of sexual assault among adolescent girls and young adult women for decades (Marcantonio et al, 2022). Thus, there is continued need for interventions designed to increase risk perception for sexual victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also carry important clinical implications, including the application of this knowledge to the development of risk-reduction programs for college women. Although the need for risk-reduction programs (e.g., those aimed at improving risk perception) would be eliminated if perpetrators ceased to engage in sexually aggressive behaviors (Orchowski & Gidycz, 2018), it is important to note that perpetrator interventions have been largely unsuccessful in producing long-term reductions in rates of violence (Orchowski & Berkowitz, 2022), resulting in stable rates of sexual assault among adolescent girls and young adult women for decades (Marcantonio et al, 2022). Thus, there is continued need for interventions designed to increase risk perception for sexual victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding NPSV, in the US some studies show that victims are more often women from ethnic minorities and young [25,26], although a recent longitudinal study found no significant association between ethnicity or age and sexual violence [27].…”
Section: Sociodemographic Characteristics Associated With Different F...mentioning
confidence: 99%
“…Within our study, we were unable to examine the intersection of SM identity, gender, and race/ethnicity due to sample size restraints. As the field moves forward, greater efforts will be needed to assess how these multiple identities influence the risk of nonconsensual sex, especially since rates of nonconsensual sex differ by various social identities (Marcantonio et al, 2022).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%